Fault-tolerant designs in lattice networks on the Klein bottle - Ayesha Shabbir (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2014)
In this note, we consider triangular, square and hexagonal lattices on the flat Klein bottle, and find subgraphs with the property that for any j vertices there exists a longest path (cycle) avoiding all of them. This completes work previously done in other lattices.